1999
DOI: 10.1046/j.1365-294x.1999.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analyses of genetic differentiation in a hybrid zone of Sorex araneus (Insectivora: Soricidae)

Abstract: Microsatellites are used to unravel the fine‐scale genetic structure of a hybrid zone between chromosome races Valais and Cordon of the common shrew (Sorex araneus) located in the French Alps. A total of 269 individuals collected between 1992 and 1995 was typed for seven microsatellite loci. A modified version of the classical multiple correspondence analysis is carried out. This analysis clearly shows the dichotomy between the two races. Several approaches are used to study genetic structuring. Gene flow is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 51 publications
11
78
3
Order By: Relevance
“…4). The genetic structure values measured in this study are globally similar to what Lugon-Moulin et al (1999a) and Brü nner et al (2002b) observed in the same hybrid zones using only seven microsatellite loci. This implies that the set of 10 loci added in this study carry similar information to the first seven loci.…”
Section: Overall Genetic Structure In the Lh And Ht Hybrid Zonessupporting
confidence: 85%
See 2 more Smart Citations
“…4). The genetic structure values measured in this study are globally similar to what Lugon-Moulin et al (1999a) and Brü nner et al (2002b) observed in the same hybrid zones using only seven microsatellite loci. This implies that the set of 10 loci added in this study carry similar information to the first seven loci.…”
Section: Overall Genetic Structure In the Lh And Ht Hybrid Zonessupporting
confidence: 85%
“…Data collection, sizing of the bands, and analysis were done using the GeneScan software (Applied Biosystems). The individuals already genotyped at some loci (L9, L16, L57, L62, and L69) in other studies (Lugon-Moulin et al 1999a;Brü nner et al 2002b) were not analyzed again for this study.…”
Section: Dna Extraction and Microsatellite Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, microsatellite mutations are known to deviate from an ideal SMM or GSM (Estoup and Angers 1998, Ellegren 2000, Xu et al 2000. A comparison of the values of F ST under a random mutation process and R ST under a strict stepwise mutation model, computed using the same data, can provide valuable insights into phylogenetic inferences, i.e., the importance of mutation vs. genetic drift or gene flow for population differentiation (Michalakis and Veuille 1996, Ross et al 1997, Estoup et al 1998, Lugon-Moulin et al 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Each allele in each locus was standardized prior to the R st calculations in order to minimize the variance due to differences in sample sizes. Slatkin's R st , which is a Wright's (1951) F stanalogue assuming a stepwise mutation model (SMM, Kimura & Crow, 1964), appears to better reflect true differentiation in highly structured populations (see Lugon-Moulin et al 1999, for a review). R st CALc software was also used to calculate N m values and du 2 genetic distance as defined by Goldstein et al (1995).…”
Section: Data Analysesmentioning
confidence: 99%